Evaluasi Kinerja dan Modifikasi Sistem Water Spray Api Basin (American Petroleum Institute Basin) Terminal Loading Area PT Pertamina Hulu Mahakam - Yudha Suherdiansyah; Mad Yusup; Purbawati Purbawati; Ida Rosanti; Diyaa Aaisyah Salmaa Putri Atmaja (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The Terminal Loading Area (TLA) API at PT Pertamina Hulu Mahakam functions as a facility for processing oily water before being discharged into the environment. One of the main issues faced is the accumulation of thick floc (oil clumps) due to high emulsions in crude oil, along with the malfunctioning water spray valve on line 1, causing operators to resort to manual spraying using hydrant water. This increases the risk of exposure to hazardous chemicals such as Benzene, Toluene, and Xylene (BTX), which poses a health threat to workers. Therefore, improvements to the water spray system are needed to reduce BTX exposure and enhance the effectiveness of oil-water separation. This study aims to analyze the effectiveness of proposed improvements to the water spray system to reduce BTX exposure and improve the efficiency of oil-water separation. The methodology used includes literature review, field study, and technical testing. Proposed solutions include replacing or repairing the damaged water spray valve, adding piping networks to compartment 2 to distribute water more evenly, and using treated water (produced water) to optimize the system and reduce reliance on hydrant water. The results of the study indicate that replacing or repairing the water spray valve, adding piping networks, and using produced water effectively reduce BTX exposure while maintaining oil recovery effectiveness. The trials also showed that using the Oil Pump (P-3230 & P-3235) provides optimal pressure (8–9 barg) for water spray, compared to the less effective Water Pump (P-3200 & P-3205). Implementing these solutions is expected to reduce BTX exposure for workers, improve oil-water separation efficiency, and contribute to a safer and more efficient working environment.